2016
DOI: 10.1038/srep29348
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of water-soluble polymer-encapsulated As4S4 to increase oral bioavailability and chemotherapeutic efficacy in AML mice

Abstract: Realgar (As4S4) has been demonstrated to be effective for the treatment of acute myeloid leukemia (AML); it has the advantages of no drug resistance and oral administration. Nevertheless, its poor solubility has been an obstacle to its bioavailability, requiring high-dose administration over a long period. We investigated whether crushing realgar crystals to the nanoscale and encapsulating the particles in a water-soluble polymer in one step using hot-melt extrusion would increase the bioavailability of As4S4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The e-As 4 S 4 was prepared according to the procedure previously reported (11). The commercial compound As 4 S 4 (powder of 28 μm in average diameter) and soluplus were mixed in a ratio of 1:15 (w/w) and fed into a co-rotating twin-screw extruder (HAAKE MiniLab II, ThermoFisher Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The e-As 4 S 4 was prepared according to the procedure previously reported (11). The commercial compound As 4 S 4 (powder of 28 μm in average diameter) and soluplus were mixed in a ratio of 1:15 (w/w) and fed into a co-rotating twin-screw extruder (HAAKE MiniLab II, ThermoFisher Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years we and other research groups have made efforts to increase its poor water solubility by reducing the original crystal size into nanoscale in different ways (1012). We have demonstrated that the bioavailability and the therapeutic effect of As 4 S 4 were increased significantly on acute myeloid leukemia (AML) in vitro and in vivo when the crystal particles were reduced into nanoscale and encapsulated with hydrophilic polymers (11). Moreover, nanoscaled As 4 S 4 also inhibited the proliferation of multiple myeloma cells (10) and melanoma cancer cells (12) effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble-As 4 S 4 showed much higher cytotoxicity towards HL-60 leukemia cells in vivo and in vitro studies than raw-As 4 S 4 ( Ma et al, 2016 ). Milling realgar into nanoparticles has more potent anti-multiple myeloma (MM) activities than arsenic trioxide (ATO), with enhanced depletion of MM stem-like SP cells and synergistic anti-MM activity with lenalidomide and melphalan ( Cholujova et al, 2017 ).…”
Section: Introductionmentioning
confidence: 92%
“…The effects of particle size and hydrothermal treatment (Powder 4 were treated at 30, 40, 50, and 100°C) on the dissolution behavior of the PNP were investigated. Dissolution studies were carried out on a dissolution apparatus (ZRS-8L, Tianda Tianfa, China) with a rotation speed of 75 rpm according to the China Pharmacopoeia apparatus paddle method [24,25] The content of notoginsenoside R 1 and ginsenosides Rg 1 and Rb 1 in the medium were determined by HPLC as described above. Because the dissolution of ingredients was affected by the particle size, the dissolution rate calculated using the revised equation is as follow:…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%